The Effect of Digital Transformation and Workplace Effectiveness on Organizational Citizenship Behavior: A Case Study at Surabaya Personnel and Human Development Agency - Suparmi, Mamik; Witjaksono, Andre Dwijanto; Kistyanto, Anang (Quantitative Economics and Management Studies, 2024)
This study aimed to examine the effect of digital transformation and workplace effectiveness on organizational citizenship behavior. This study used cross-sectional survey research design with quantitative research approach to address the objectives. There were sixty-two employees of Surabaya personnel and human development agency (BKPSDM Surabaya) involved as the respondents. They were chosen using voluntary sampling technique. Data were collected using a questionnaire with six-point Likert’s scaling method comprising of measuring the three variables. Data were then analyzed using descriptive statistics and multiple linear regression to portray the depiction of employees perceived digital transformation, workplace effectiveness, and organizational citizenship behavior and to reveal the correlational nexus between variables. Results showed that employees perceived digital transformation, workplace effectiveness, and organizational citizenship behavior were in a very high category (Swanson’s Q = Q4). Another finding showed that digital transformation and workplace effectiveness affected the formation of organizational citizenship behavior.